Layered bismuth copper oxychalcogenides as advanced photothermal materials for efficient interfacial solar desalination - Shridharan, Tatachari Santhanagopalan; Kang, Min Je; Sivanantham, Arumugam; Kim, Sungkyu; Cho, In Sun (Desalination, 2022)
Interfacial solar desalination is a promising method to sustainably address global water scarcity. Thus far, it has been a challenge to find photothermal materials with both efficient light absorption and low thermal conductivity. This study is the first to explore a layered oxychalcogenide of bismuth copper oxysulfide (BiCuSO, BCSO) nanosheets as a promising photothermal absorber material for interfacial solar desalination. We show that the two-dimensional layered crystal structure of BCSO enables anisotropic thermal transport. At the same time, the nanosheet morphology induces nanoporous coating due to a nano-clustering effect when it is coated on substrates, leading to a rough surface, nano-porosity, and substantial heat confinement. Significantly, BCSO nanosheets show attractive properties such as intense light absorption (up to 1040 nm), low thermal conductivity (0.099 W/m·K), strong heat confinement and excellent wettability. With capillary water supply and porous polyurethane structure, BCSO nanosheets demonstrated a high water-evaporation rate (1.77 kg/m2·h), solar-to-thermal conversion efficiency (96 %), and stable long-term evaporation performance under simulated sunlight irradiation. Furthermore, condensed vapors from seawater met the World Health Organization's drinking standard, proving the strong ion rejection capability of BCSO. Our results provide new insights into developing efficient photothermal materials for enhanced interfacial solar-powered desalination systems.
Keywords: Absorber material; BiCuSO nanosheet; Interfacial solar desalination; Layered oxychalcogenide; Layered Structures; Low thermal conductivity; Oxychalcogenides; Photo-thermal; Solar desalination; Water scarcity; BiCuSO nanosheet; Interfacial solar desalination; Layered structure; Oxychalcogenides; Thermal conductivity